Collaborative Leadership in Elementary Education: A Systematic Review of Effective Principal Practices - Nurlina Nurlina; Danny Meirawan; Cepi Triatna; Suyadi Suyadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Collaborative leadership in elementary schools is seen as strategic to address the complexity of education management, although its implementation still faces various challenges. This study systematically examines the collaborative leadership practices of elementary school principals with a focus on principles, managerial strategies, and implementation barriers. A literature review of 14 articles published from 2019 to 2025 obtained through google scholar, Sinta, Garuda, and ScienceDirect. Selection is based on topic relevance, school context, and focus on collaborative leadership. Collaborative leadership is rooted in participation, openness, and shared responsibility. The principal acts as a facilitator who encourages the involvement of teachers, staff, parents, and curriculum development. Prominent strategies include role sharing, deliberation, professional coaching, and external collaboration. The main obstacles are individualistic work culture, limited leadership capacity, and lack of policy support. The success of collaborative leadership is not only determined by the principal's vision, but also by the ability to build a sustainable collaborative climate. These findings contribute to the educational leadership literature and practical implications for principals and policymakers. Further research is suggested to explore the impact of collaborative leadership on student learning outcomes and teacher professional development.